2022
DOI: 10.1097/phm.0000000000002045
|View full text |Cite
|
Sign up to set email alerts
|

SARcopenia Assessment in Hypertension: The SARAH Study

Abstract: Objectives:The aims of the study were to investigate the relationship between sarcopenia and renin-angiotensin system-related disorders and to explore the effects of angiotensin-converting enzyme inhibitors and angiotensin II receptor blockers on muscle mass/function and physical performance. Design: This multicenter, cross-sectional study was performed using ISarcoPRM algorithm for the diagnosis of sarcopenia. Results: Of the 2613 participants (mean age = 61.0 ± 9.5 yrs), 1775 (67.9%) were hypertensive. All s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
21
1
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 33 publications
(113 reference statements)
1
21
1
2
Order By: Relevance
“…In addition, there was significant interaction between sarcopenia and hypertension, and the stratified analyses showed stronger associations between sarcopenia and primary outcome in individuals with hypertension. Previous study had found sarcopenia-related parameters (muscle mass/function and physical performance) were independently and negatively related to hypertension (34,35) . While hypertension was also with increased risk of sarcopenia.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…In addition, there was significant interaction between sarcopenia and hypertension, and the stratified analyses showed stronger associations between sarcopenia and primary outcome in individuals with hypertension. Previous study had found sarcopenia-related parameters (muscle mass/function and physical performance) were independently and negatively related to hypertension (34,35) . While hypertension was also with increased risk of sarcopenia.…”
Section: Discussionmentioning
confidence: 94%
“…While hypertension was also with increased risk of sarcopenia. In patient with anti-hypertensive drugs use, anti-hypertensive drugs use seems to be related to higher muscle mass and gait speed values, and angiotensin converting enzyme inhibitors use is more likely to be related to higher muscle function only in female patients (35) . In light of these findings, it might be worth paying more attention to screen sarcopenia in hypertensive individuals.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that a high dietary inflammatory diet cause an elevated risk of developing sarcopenia, 36 with higher levels of dietary inflammation amplifying this risk. Moreover, studies exploring the association between sarcopenia and conditions correlated with the renin‐angiotensin system have found that hypertension can negatively affect muscle mass, physical function and double the risk of sarcopenia 37 . In terms of dietary strategies aimed at hypertension prevention, Sanaz and coworkers 38 observed no substantial correlation between adherence to such diets and the likelihood of developing sarcopenia.…”
Section: Discussionmentioning
confidence: 99%
“…Other than older age, and increased weight and duration of DM had positive and independent impact concerning the presence of sarcopenia. Recently, it has been shown that the presence of DM was negatively related with handgrip strength values [17]. Moreover, a longitudinal study has also reported that chronic conditions such as cardiovascular disease, hypertension and DM were associated with a rapid decline of handgrip strength [31].…”
Section: Discussionmentioning
confidence: 99%